Post-caesarean section pain and quality of sleep among mothers who delivered by caesarean section under spinal anesthesia - Ririn Harini; Juwitasari Juwitasari; Lilis Setyowati; Rifdah Dita Oktavia (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2021)
Background: Post caesarean section mothers commonly feel pain in the post-operative area during the wound healing process. Most post-operative mothers feel the pain sensation as a disturbance and lowering their quality of sleep.Purpose: To determine pain level and identify the relationship of pain level and sleep quality among mothers who delivered by caesarean section under spinal anaesthesia.Method: The descriptive non-experimental correlative study design identified 50 mothers from Inpatient Ward Wava Husada Hospital of Kepanjen, Malang, East Java, Indonesia at April 2020. The Post-caesarean section pain level identified by using the Numeric Rating Scale (NRS) and the sleep quality is measured using Pittsburgh Sleep Quality Index (PSQI) questionnaire.Results: 38 mothers (76%) had severe pain level and most of them (43 mothers) had poor sleep quality. The Spearman correlation test showed that there was a relationship between the Post-caesarean section pain level and sleep quality, p value = 0.000 (p <0.05) and r = 0.314.Conclusion: The post-caesarean section pain levels among mothers who delivered by caesarean section under spinal anaesthesia should be identified earlier as we would like to encourage the nursing staff to give further intervention to maintain their sleep quality.